Respiratory diseases and the gut microbiota: an updated review - Yu, Xin; Yu, Xiao; Wang, Yubo; Guo, Xiaoping; Wang, Chao; Wang, Fang (Frontiers in Cellular and Infection Microbiology, 2025)
The gut microbiota constitutes a vital ecosystem within the human body playing a pivotal role in immune regulation and metabolic homeostasis. Emerging research underscores a sophisticated interplay between the gut and lungs, termed the “gut-lung axis.” Gut microbes exert influence over pulmonary immunity and metabolism via immune mediators (e.g., cytokines and interleukins), metabolites (e.g., short-chain fatty acids) and direct microbial translocation. Dysbiosis of the gut microbiota has been implicated in a spectrum of respiratory diseases, including asthma, chronic obstructive pulmonary disease (COPD), acute lung injury (ALI), Coronavirus Disease 2019 (COVID-19), lung cancer, idiopathic pulmonary fibrosis (IPF), pulmonary arterial hypertension (PAH), acute lower respiratory infection (ALRI) and tuberculosis (TB). Although multi-omics technologies have elucidated certain mechanisms underlying the gut-lung axis, numerous pathways remain to be fully delineated. This review synthesizes current knowledge on the role of gut microbiota and their metabolites in respiratory diseases and assesses their therapeutic potential. Future investigations should prioritize strategies to restore and maintain microbial homeostasis, such as dietary modifications, probiotic supplementation and fecal microbiota transplantation to pioneer novel preventive and therapeutic approaches. These summaries of advances in gut microbiology research promise better management and exploration of therapeutic strategies for respiratory diseases.